Impact of Industrial Noise on Production Efficiency - Osamah Ibrahim Ali Barka; Abdulqadir M. Alhadar; Musbag Ahedery; Omer I. A. Hmellah; Nuri Salem Ali Abosetha; Ahmed Alnagrat (PERFECT: Journal of Smart Algorithms, 2026)
Industrial noise is a common problem in manufacturing environments because it affects occupational comfort, machine reliability, and production efficiency. Objective: This study examines whether acoustic monitoring and sound pressure level measurement can be used to connect industrial machinery noise with output losses and maintenance needs. Methods: The method combined machine observation, acoustic signal recording, cutter cycle timing, production counting, and comparative analysis of a pasta packaging machine, lathe, multi-spindle drilling machine, and cigarette production machine. Results: The pasta packaging machine showed the clearest relationship between noise behavior and productivity. Its cutter was designed to operate every one and one-half seconds, but the measured acoustic rhythm indicated an average cycle of about one and two-thirds seconds. This timing difference reduced output from four hundred to three hundred sixty-one bags in ten minutes, equal to a loss of about ten percent. Other machines with higher sound pressure levels also showed signs of wear, vibration, and reduced operational stability. Conclusion: Industrial machinery noise is not only a workplace hazard but also a practical indicator of machine condition. The study supports using noise control, maintenance, acoustic monitoring, industrial machinery assessment, and production efficiency evaluation as an integrated approach for improving reliability and manufacturing performance.